DAMPAK COVID-19 PADA PENDAPATAN PETANI MELON DI WILAYAH KECAMATAN WATES - REDY KHOIRIANTO; Endah Masrunik (Universitas Islam Balitar, 2022)
Covid-19 has had a significant impact on various sectors in Indonesia. One of them is economics. The community's economy has decreased due to restrictions in the Covid era, besides the declining economy has caused people's purchasing power to also decrease. So this study aims to determine the impact of the Covid-19 pandemic on the income of melon farmers in Purworejo Village, Wates District, Blitar Regency. This research method uses qualitative research. The data collection methods used in this study were observation, documentation, and interviews. The results showed that with the Covid-19 pandemic the income of melon farmers decreased significantly. The price of melons for types A and b decreased by about 20%, while for melons type C the decline was up to 50%. So from this decline, the sales income of melon farmers decreased from Rp. 2000, - to Rp. 5000, - / kg. To avoid selling with big losses, melon farmers sell their harvests in bulk. In addition, melon farmers also prefer not to join the partnership.